Environmental torques acting on a low Earth orbiter cylindrical spacecraft - Zanardi, M. C.; Real, F. F. (Elsevier B.V., 2003)
Classical models of gravity gradient, solar radiation, aerodynamic and magnetic torques acting on a circular cylinder satellite. The magnitude of each such are compared with parameterization in terms of the dimensions of the satellite and its altitude in relation to the Earth's surface. Two different satellite data are considered. The results agree with the classical results and show that for altitude between 0 and 800 km the gravity gradient, aerodynamic and magnetic torques decrease with altitude while the solar radiation torque is almost independent of the altitude. The relative importance of these torques depends on the size, mass, moments of inertia and altitude of the satellite. The results can be useful to propagate the satellite attitude, to satellite missions analysis and to validate the analytical approaches. (C) 2003 COSPAR. Published by Elsevier B.V. Ltd. All rights reserved.